Hydrological methodology evolution for runoff estimations at ungauged sites - Şen, Zekâi (MDPI, 2023)
This review paper recites fundamentals of historical runoff estimation methodologies that were developed for ungauged drainage basins. Additionally, new approaches are also provided as extensions of modern ones. Early methodologies of runoff calculations were suggested towards the end of the 18th century, when there was no historical record availability for rainfall or runoff. Some of these methodologies have not been cited in the scientific literature, but they have been frequently used by engineers as practical hydrological approaches in different parts of the United States, especially in Kansas. Early hydrologists were aware of the shortcomings, but they were hampered by the shortage of reliable streamflow and rainfall data. These methods did not consider recurrence intervals associated with designs, and their drawbacks originated more from a shortage of useful hydrologic data rather than logical and rational interconnection between the causative and resultant factors. With availability of measured data, early studies considered daily total rainfall amounts for design purposes, which continued until 1935 when reliable rainfall frequency maps were published for durations shorter than 24 h. Frequency analysis advancement in 1940s provided regional flood frequency methods for ungauged sites. The transition to modern frequency-based hydrologic methods started from 1950 onwards. It is the main purpose of this review paper to cite the early and recent simple methodologies for ungauged drainage area rainfall, especially runoff estimation works. This paper provides the logical and rational fundamentals of each approach so that the reader may become acquainted with the evolution of the hydrological studies.
Keywords: Bridge; Catchment; Culvert; Evolution; Hydrology; Methodology; Ungauged; Rational; Runoff